Light-Induced Metal-Free Catalyzed C–H Alkylation of (Iso)Quinolines - Wang, Qing; Mei, Guangyao; Luo, Zi Jin; Sun, Xiaotong; Weng, Jianquan; Zhang, Guofu (Synlett, 2025)
A new method for preparing alkylated (iso)quinolines with substituted (iso)quinolines and alkanes as substrates, PIFA as an oxidant, and Rose bengal as a photosensitizer under 50 W light irradiation is proposed. Diverse structures were shown to be tolerated under optimal conditions, and a series of alkylated products were obtained in the desired yields. Compared with previous reactions using aldehydes and carboxylic acids as carbon sources, this method uses simple alkanes as carbon sources, offering good chemical stability and high atom economy.
Keywords: (iso)quinolines; cycloalkanes/straight alkanes; visible light; alkylation; Rose bengal